The Effect of the Operational Exit Tolls on the Welfare of the Local Community - Inayati Nuraini Dwiputri; Albertus Girik Allo; Linda Seprillina; Ermita Yusida (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2022)
Infrastructure is a part of accelerating economic growth. The construction of toll roads can provide positive and negative impacts. The existence of toll roads can reduce transportation and production costs, which will increase domestic and international market efficiency. However, the construction of toll roads is feared can kill small businesses. Studies of the effect of operational exit tolls on welfare are still limited in Indonesia. This study was conducted to identify the impact of toll roads on community welfare in the Pandaan-Malang exit tolls area. Using paired t-test and the cluster analysis method showed that the positive and negative impacts of toll roads construction on the community in the exit tolls area are varied for each cluster. This study can be used as the basis for formulating policies for communities affected by operational exit tolls, in particular. Creating new economic centers in the exit tolls based on local uniqueness can minimize the negative impacts on communities.How to Cite:Dwiputri, I.N., Allo, A.G., Yusida, E. & Seprillina, L. (2022). The Effect of the Operational Exit Tolls on the Welfare of the Local Community. Signifikan: Jurnal Ilmu Ekonomi, 11(1), 73-82. https://doi.org/10.15408/sjie.v11i1.22108.